Estimation of microbial protein synthesis in the rumen of growing lambs based on the purine derivative excretions and the dietary forage-to-concentrate ratio - Mahboobi, Zahra; Karimi , Naser; Jahanbakhshi, Abbas (Journal of Advanced Veterinary and Animal Research, 2023)
Objective: Estimating microbial protein synthesis (MPS) in the rumen of growing lambs based on the urinary excretion of purine derivatives (PDs) and forage to concentrate (F/C) ratio. Materials and Methods: 36 similar-growing male lambs (weight 32.53 ± 1.90 kg; age 93 ± 6.63 days) were used in a completely randomized design with four groups: a) the 20–80 F/C ratio (dry hay 10% + wheat straw 10%), b) the 20–80 F/C ratio (dry hay 0% + wheat straw 20%), c) the 10–90 F/C ratio (dry hay 5% + wheat straw 5%), d) and the 10–90 F/C ratio (dry hay 0% + wheat straw 10%) with nine replicates. Results: Total PD and rumen MPS synthesized increased (10.98 vs. 13.25 mmol/day and 59.45 vs. 71.80 gm/day) in group d compared to group a. Dry organic matter intake (0.869 kg/day), fermentable dry organic matter (0.563 kg/day), and microbial nitrogen (N) yield (11.48 gm/day) of group d were at the maximum, but in terms of gN/kg dry organic matter (22.37 gm/kg), the mean of group c was higher than others. Conclusion: Increasing the level of food concentrate and the gradual removal of alfalfa from the diet increased the excretion of PD and MPS in the rumen. It was also found that urinary PD monitoring is an accurate indicator for the estimation of MPS. J. Adv. Vet. Anim. Res., 10(3): 385–394, September 2023 http://doi.org/10.5455/javar.2023.j691